Counseling Women and Education in Era 4.0 - Umi Kulsum; Ari Kartini; Ai Siti Julaeha (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract Women are central in life. Of course, women's education has an important role, so women need to get a higher education. In Babakan village, Sindangsuka village, many women are still teenagers but are married and even have children. This makes the mothers do not have the maximum education to educate their children. The average is elementary, junior high, high school and a very small proportion are college graduates. The service is carried out using a n expository method, by providing an understanding of the importance of education at all levels of society, especially parents. In addition, by collecting information on the educational background of women in this area. This activity had a positive result, namely a change in people's views about the importance of education for women. In addition, this activity also provides direction and motivation for teenagers to continue their education to a higher level. Activities like this need to be continued, because in the Garut area there are still many people who are not aware of the importance of education, especially for women Abstrak Perempuan merupakan sentral dalam kehidupan. Tentu saja dalam pendidikan perempuan memiliki peran penting, maka pendidikan yang tinggi perlu dienyam oleh para perempuan. Di kampung Babakan desa Sindangsuka banyak perempuan yang masih remaja akan tetapi sudah menikah bahkan memiliki anak. Hal tersebut menjadikan para ibu tersebut belum memiliki pendidikan yang maksimal untuk mendidik putra-putrinya. Rata-rata SD, SMP, SMA dan sebagian kecil sekali yang merupakan lulusan perguruan tinggi. Pengabdian dilakukan dengan metode ekspositori, dengan memberikan pemahaman terkait pentingnya pendidikan pada semua lapisan masyarakat, terutama para orang tua. Selain itu dengan, mengumpulkan informasi mengenai latar belakang pendidikan para perempuan di daerah ini. Kegiatan ini mendapatkan hasil yang positif yaitu perubahan pandangan masyarakat tentang pentingnya pendidikan bagi perempuan. Selain itu, kegiatan ini pun memberikan arahan dan motivasi pada para remaja untuk melanjutkan pendidikan ke jenjang yang lebih tinggi. Kegiatan seperti ini perlu terus dilakukan, karena di daerah Garut masih banyak masyarakat yang kurang sadar akan pentingnya pendidikan terutama untuk para perempuan.